2020
DOI: 10.1002/ppul.25032
|View full text |Cite
|
Sign up to set email alerts
|

Congenital lung abnormality quantification by computed tomography: The CLAQ method

Abstract: Introduction: To date, no consensus has been reached on the optimal management of congenital lung abnormalities, and factors predicting postnatal outcome have not been identified. We developed an objective quantitative computed tomography (CT) scoring method, and assessed its value for clinical decision-making. Methods: Volumetric CT-scans of all patients born with a congenital lung abnormality between January 1999 and 2018 were assessed. Lung disease was quantified using the newly-developed congenital lung ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The relation between mediastinal shift and long-term outcome is yet to be investigated. Somewhat surprisingly, the COS produced in this study does not include outcome parameters directly linked to lesion size, even though several studies found a correlation between lesion size and symptom development [ 40 , 41 ]. However, lesion size can be linked to mediastinal shift to a certain degree, as a large lesion will have a higher chance of causing this shift.…”
Section: Discussionmentioning
confidence: 77%
“…The relation between mediastinal shift and long-term outcome is yet to be investigated. Somewhat surprisingly, the COS produced in this study does not include outcome parameters directly linked to lesion size, even though several studies found a correlation between lesion size and symptom development [ 40 , 41 ]. However, lesion size can be linked to mediastinal shift to a certain degree, as a large lesion will have a higher chance of causing this shift.…”
Section: Discussionmentioning
confidence: 77%
“…CPAM development/postsurgical appearance on chest CT imaging—scored according to the congenital lung abnormality quantification (CLAQ) method. 51 …”
Section: Methods and Analysismentioning
confidence: 99%
“…The radiological appearance of the CPAM on CT imaging will be scored according to the previously published CLAQ-method, and compared between the treatment groups using the Mann-Whitney U test. 51 …”
Section: Methods and Analysismentioning
confidence: 99%
“…Hybrid samples meeting aforementioned histological criteria as well as systemic arterial blood supply, were also included. Patients were excluded if CT-scans did not allow reliable scoring, such as CT-scans with a slice thickness exceeding 3 mm, or with poor image quality, or a large pneumothorax [36] .…”
Section: Methodsmentioning
confidence: 99%
“…Clinical data were obtained from the electronic patient records and included neonatal data and information on the surgical procedure. In our center, we adhere to a wait-and-see policy for all CLA patients unless they exhibit symptoms, such as respiratory distress, recurrent infections or cardiac volume overload [36] . Lung disease on chest CT was quantified using the newly-developed congenital lung abnormality quantification (CLAQ) scoring method [36] .…”
Section: Methodsmentioning
confidence: 99%